Gambaran resiko delirium pada pasien gagal ginjal kronik - Anjali, Nabila; Subandi, Andi; Sari, Lisa Anita; Rudini, Dini; Ekaputri, Kintan Resqhita (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: The lack of data describing the risk of delirium in patients with chronic kidney disease, particularly the elderly, and the lack of routine delirium screening using the AWOL Score at Raden Mattaher Hospital in Jambi have the potential to cause delays in the early detection of delirium. Purpose: to determine the risk of delirium in patients with chronic kidney failure. Method: This quantitative study, with a descriptive observational design using a cross-sectional approach, was conducted at Raden Mattaher Hospital in Jambi. Sampling was conducted using an accidental sampling technique on 92 elderly patients with chronic kidney disease undergoing hemodialysis. Delirium risk was measured using the AWOL Score with univariate data analysis. Results: Patients with chronic kidney disease (CKD) were predominantly elderly, aged 60–65 years, and male (53.3%), with the longest duration of illness ranging from 6 months to 1 year (40.2%). Based on the AWOL score, most patients were in the low-risk delirium category (40.2%), followed by very low-risk (29.3%), and high-risk (26.1%), while only a small proportion were at high to very high risk. Conclusion: Based on the AWOL score, most patients were in the low-risk delirium category, although patients with moderate to very high risk were still found. Keywords: AWOL Score for Delirium; Chronic Kidney Disease; Delirium. Pendahuluan: Kurangnya data mengenai deskripsi risiko delirium pada pasien gagal ginjal kronis khususnya kelompok lansia, dan kurangnya skrining delirium secara rutin menggunakan instrumen AWOL Score di Rumah Sakit Raden Mattaher Jambi berpotensi menyebabkan keterlambatan deteksi dini delirium. Tujuan: untuk mengetahui gambaran resiko delirium pada pasien gagal ginjal kronik. Metode: Penelitian kuantitatif dengan desain deskriptif observasional menggunakan pendekatan cross sectional, yang dilakukan di Rumah Sakit Raden Mattaher Jambi. Pengambilan sampel dilakukan menggunakan teknik accidental sampling pada 92 pasien lansia dengan gagal ginjal kronis yang menjalani hemodialisis, dan pengukuran risiko delirium menggunakan instrumen AWOL Score dengan analisis data univariat. Hasil: Pasien gagal ginjal kronis didominasi oleh lansia berusia 60–65 tahun dan laki-laki (53.3%) dengan durasi penderitaan terlama 6 bulan–1 tahun (40.2%). Berdasarkan penilaian Skor AWOL, sebagian besar pasien berada dalam kategori risiko delirium rendah (40.2%), diikuti oleh risiko sangat rendah (29.3%), dan risiko tinggi (26,1%), sedangkan hanya sebagian kecil yang memiliki risiko delirium tinggi hingga sangat tinggi. Simpulan: Berdasarkan penilaian Skor AWOL, sebagian besar pasien berada dalam kategori risiko delirium rendah, meskipun pasien dengan risiko sedang hingga sangat tinggi masih ditemukan. Kata kunci : Awol Score for Delirium; Delirium; Gagal Ginjal Kronik.